2021
DOI: 10.12688/gatesopenres.13228.1
|View full text |Cite
|
Sign up to set email alerts
|

Refining livestock mortality indicators: a systematic review

Abstract: Background: Livestock mortality impacts farmer livelihoods and household nutrition. Capturing trends in livestock mortality at localised or national levels is essential to planning, monitoring and evaluating interventions and programs aimed at decreasing mortality rates. However, livestock mortality data is disparate, and indicators used have not been standardised. This review aims to assess livestock mortality indicator definitions reported in literature, and define the ages where mortality has greatest impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 89 publications
(71 reference statements)
2
22
0
Order By: Relevance
“…Regarding disease-associated mortality, our review findings indicate that data are remarkably scarce for Ethiopia and are mostly in the context of surveys or outbreak investigations. The studies identified reported on mortality in Oromia, SNNPR, Amhara and Tigray, but age was often not recorded, however young stock mortality is generally considered high in Sub-Saharan Africa and approximately ranges from 9% to 45% (Wymann et al ., 2006; Bolajoko et al ., 2020; Wong et al ., 2021). The reported mortality percentages ranged from 1 to 25% for studies published from 2010 to 2019, although no clear definition of the measure of mortality was provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding disease-associated mortality, our review findings indicate that data are remarkably scarce for Ethiopia and are mostly in the context of surveys or outbreak investigations. The studies identified reported on mortality in Oromia, SNNPR, Amhara and Tigray, but age was often not recorded, however young stock mortality is generally considered high in Sub-Saharan Africa and approximately ranges from 9% to 45% (Wymann et al ., 2006; Bolajoko et al ., 2020; Wong et al ., 2021). The reported mortality percentages ranged from 1 to 25% for studies published from 2010 to 2019, although no clear definition of the measure of mortality was provided.…”
Section: Discussionmentioning
confidence: 99%
“…The reported mortality percentages ranged from 1 to 25% for studies published from 2010 to 2019, although no clear definition of the measure of mortality was provided. This is an unsurprising finding, as measuring ruminant mortality in LMICs can prove challenging due to the significant under-reporting of livestock losses and the limited baseline data in livestock numbers (Catley et al ., 2014; Wong et al ., 2021). Moreover, mortality rates are higher when reported in farmer surveys; this might be attributed to the assignment of livestock culling or sales in this category by the respondents or the underestimation of other concurrent factors that can cause livestock mortality, such as poor nutrition, mycotoxins etc.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this study did not observe increased mortality in young stock compared to adults, as young stock mortality is generally considered high in sub-Saharan Africa, which leads us to question farmer recall and whether they remember adult losses more than young stock. Wong et al (2021) also highlighted that there was a high degree of variability in both causes and risk factors which meant that ‘mortality rate’ was an incomplete indicator, and as such, qualitative and quantitative data on mortality causes would improve the understanding and allow preventative actions. Information is required on the causes of mortality for decision-making, as well as the rates in different livestock species (Catley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Tsouloufi et al recently established a systematic mapping protocol to review the available evidence on disease prevalence and associated mortality in ruminants in Ethiopia, in attempt to address the disparate data and to improve decision-making on disease control policies (Tsouloufi et al, 2020). A recent systematic review by Wong et al (2021) observed that the greatest proportion of mortalities in cattle, sheep and goats was reported to be in those under the age of six months. Interestingly, this study did not observe increased mortality in young stock compared to adults, as young stock mortality is generally considered high in sub-Saharan Africa, which leads us to question farmer recall and whether they remember adult losses more than young stock.…”
Section: Running Titlementioning
confidence: 99%
See 1 more Smart Citation